Factors Affecting Shilaturrahim As an Effort to Repair a Broken Rope Post Election - Ari Zumardin (International Journal of Advanced Multidisciplinary, 2023)
The factors that affect shilaturrahim as an effort to reconnect the broken rope after the election , is a scientific literature review article. The purpose of writing this article is to build a hypothesis of influence or role between variables that will be used in further research, within the scope of Islamic Education Management. The article writing method is the library research method, which comes from online media such as Google Scholar, Mendeley and other academic online media . Qualitative descriptive analysis . The results of this article are: 1) Silaturrohim solutions to solve any problem no matter how big; 2) Elections that are not healthy can be a factor that affects silaturrohim; 3) Understanding the importance of silaturrohim is the motivation to connect broken silaturrohim.